Astragaloside IV inhibits atherosclerosis caused by ferritin autophagy in a lipid deposition environment by activating Nrf2 - Dandan Liu; Hewei Qin; Guanghua Liu; Yang Gao; Yu Guo (Journal of Functional Foods)
Abstracts: The Chinese medicine Astragalus mongholicus Bunge has the effect of benefiting vital energy and activating blood circulation, and is commonly used clinically in the treatment of various cardiovascular diseases. Astragalus is not only a kind of traditional Chinese medicine, but is now also widely used in various kinds of health food. Astragaloside IV is the most abundant active ingredient in this herb. In addition, astragaloside IV has lipid-modulating and antioxidant pharmacological potential. The vasoprotective and anti-ferroptosis effects of astragaloside IV were determined by establishing a high-fat-fed ApoE−/− mouse model of AS and an ox-LDL-induced model of lipid damage in VECs. Lipid profile (TC, TG, LDL-C, HDLC), HE and local oil red O showed a reduction in atherosclerotic pathological damage and lipid deposition after astragaloside IV treatment. Astragaloside IV was then able to increase FTH1 and p62 expression, decrease NCOA4 and Beclin1 expression, and inhibit ferritin autophagy by activating Nrf2. Meanwhile, when ML385 inhibits Nrf2, astragaloside IV can diminish the expression of divalent iron, suppress iron death-related factors (FTH1, FTL, FPN, ACSL4), and alleviate disorders in iron metabolism and the overproduction of ROS. Collectively, these findings suggest that astragaloside IV can regulate autophagy-dependent NCOA4 and FTH1 expression through activation of Nrf2, thereby inhibiting autophagy.